STUDY OF ANALGESIC AND ANTI-INFLAMMATORY EFFECTS OF Impatiens balsamina LEAVES IN ALBINO RATS - DEBASHREE N; A SUBHALAKSHMI; S RITA; A PFUZIA (International Journal of Pharma and Bio Sciences, 2013)
To study the analgesic and anti-inflammatory effects of aqueous extract of Impatiens balsamina leaves in suitable animal models, the leaves of Impatiens balsamina were extracted with distilled water using Soxhlet apparatus. The extract thus obtained was screened for analgesic and anti-inflammatory activity using tail flick method and carrageenan induced paw oedema method in albino rats respectively. The aqueous extract of the plant produced significant increase in the reaction time at 30, 60 and 120 minutes as compared to respective controls in albino rats (p<0.05-0.001).The aqueous extract of the plant produced significant reduction in the mean increase in paw volume; 0.316±0.04 (p<0.01), 0.266±0.03 (p<0.01) and 0.166 ± 0.04 (p<0.01) at the doses of 500,1000 and 2000 mg/kg body weight respectively as compared to the control (0.483± 0.03).However the extract was found to be less effective than the standard drug. The study demonstrates significant analgesic and anti-inflammatory effects of aqueous extract of Impatiens balsamina leaves.